2011
DOI: 10.1088/0031-9155/56/5/004
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and workflow for PET monitoring of therapeutic ion irradiation: a comparison of in-beam, in-room, and off-line techniques

Abstract: An independent assessment of the dose delivery in ion therapy can be performed using positron emission tomography (PET). For that a distribution of positron emitters which appear as the result of interaction between ions of the therapeutic beam and the irradiated tissue is measured during or after the irradiation. Three concepts for PET monitoring implemented in various therapy facilities are considered in this paper. The in-beam PET concept relies on the PET measurement performed simultaneously to the irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
90
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 15 publications
0
90
0
Order By: Relevance
“…Off-line PET delivers very promising results using only one radiation field and a minimum delay, it is the method of choice when the PET/CTscanner is already installed and a practical solution is sought, although the optimum compromise in terms of imaging performances and cost-effectiveness seems to be the in-room scanner nowadays [14].…”
mentioning
confidence: 99%
“…Off-line PET delivers very promising results using only one radiation field and a minimum delay, it is the method of choice when the PET/CTscanner is already installed and a practical solution is sought, although the optimum compromise in terms of imaging performances and cost-effectiveness seems to be the in-room scanner nowadays [14].…”
mentioning
confidence: 99%
“…When using in-beam PET, the reconstructed images are closer to the original β + distribution than the images obtained from in-room and off-line acquisitions since physical decay and wash-out are minimized. In Shakirin et al (2011) it is demonstrated that in-beam PET is the best method in terms of count rate.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic comparison of these modalities shows that off-beam monitoring is not recommended, except for some specific tumours or unless the PET system is placed in the same treatment room (i.e., in-room) (Shakirin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the effect is either a broadening of the β + activity spatial distribution or a paralysis of the acquisition system due to excessive random coincidence data that do not carry any information regarding the β + distribution (Enghardt et al 1999, Parodi et al 2002. Thus, state of the art in-beam PET solutions are only applicable to synchrotron-based facilities and their effectiveness is limited by the accelerator duty cycle (Nishikido et al 2010, Tashima et al 2012, Nishio et al 2010, Shakirin et al 2011.…”
Section: Introductionmentioning
confidence: 99%